A multi-objective ant colony optimization algorithm based on the Physarum-inspired mathematical model - Yuxin Liu; Yuxiao Lu; Chao Gao; Zili Zhang; Li Tao (2014 10th International Conference on Natural Computation (ICNC), 2014)
Multi-objective traveling salesman problem (MOTSP) is an important field in operations research, which has wide applications in the real world. Multi-objective ant colony optimization (MOACO) as one of the most effective algorithms has gained popularity for solving a MOTSP. However, there exists the problem of premature convergence in most of MOACO algorithms. With this observation in mind, an improved multi-objective network ant colony optimization, denoted as PM-MONACO, is proposed, which employs the unique feature of critical tubes reserved in the network evolution process of the Physarum-inspired mathematical model (PMM). By considering both pheromones deposited by ants and flowing in the Physarum network, PM-MONACO uses an optimized pheromone matrix updating strategy. Experimental results in benchmark networks show that PM-MONACO can achieve a better compromise solution than the original MOACO algorithm for solving MOTSPs.